1979
DOI: 10.1139/f79-132
|View full text |Cite
|
Sign up to set email alerts
|

Swimming Behavior of Salmonid Fish in Ocean Pens

Abstract: Based on personal observations and questionnaires to Norwegian fish farmers, the behavior of three species and several different stocks of salmonid fish reared in ocean pens is described. Swimming activity and the constancy of swimming orientation (clockwise or counter clockwise) vary among species. With few exceptions, the orientation of Atlantic salmon (Salmo salar) at any one farm does not change with tide, season, or age offish. Stock origin and/or the early rearing history may impose this directionality. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
2

Year Published

1988
1988
2016
2016

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 0 publications
3
23
2
Order By: Relevance
“…In the marine life stages, wild salmonids swim on average at 1 body length (BL) s −1 (Drenner et al 2012). This is similar to observed swimming speeds in salmon farms (Sutterlin et al 1979, Kadri et al 1991, Blyth et al 1993, Juell & Westerberg 1993. In the wild, this cruising speed is suggested to be the energetic optimum with lowest cost of transport (Drenner et al 2012).…”
Section: Introductionsupporting
confidence: 66%
“…In the marine life stages, wild salmonids swim on average at 1 body length (BL) s −1 (Drenner et al 2012). This is similar to observed swimming speeds in salmon farms (Sutterlin et al 1979, Kadri et al 1991, Blyth et al 1993, Juell & Westerberg 1993. In the wild, this cruising speed is suggested to be the energetic optimum with lowest cost of transport (Drenner et al 2012).…”
Section: Introductionsupporting
confidence: 66%
“…Schooling salmon swim continuously, but not at a constant speed. Swimming speeds that average from 0.2 to 1.9 body lengths per second (BL s -1) have been observed (Sutterlin et al, 1979;Kadri et al, 1991;Blyth et al, 1993;JueU and Westerberg, 1993;Smith et al, 1993). Swimming speed seems to increase towards the edge of the cage (Sutterlin et al, 1979;Fernti et al, 1988) and varies with season (Fern0 et al, 1988;Juell and Westerberg, 1993) and time of day.…”
Section: Group Structure: An Indicator Of Well-being?mentioning
confidence: 99%
“…GROUP BEHAVIOUR Direct observation through a pair of polarized glasses is a valuable and simple method of recording the main modes of behaviour in high-density groups of fish in sea cages. Using this method Sutterlin et al (1979) found that the swimming direction of Atlantic salmon may differ between cages at one farm, but usually does not change with tide, season or age in one particular cage. Stock-related swimming behaviour (Fern6 et al, 1988), hunger-dependent surface activity during feeding (Juell, 1988;Blyth et al, 1993) and stress-related leaping activity have also been recorded by this method.…”
Section: Observing Behaviour In Sea Cagesmentioning
confidence: 99%
See 2 more Smart Citations